2015
DOI: 10.1016/j.coviro.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deficiency and polymorphisms of cyclophilin A reveal its essential role for Human Coronavirus 229E replication

Abstract: Replication of coronaviruses is inhibited in vitro by cyclosporin A, a well-known immunosuppressive drug which binds to cellular cyclophilins thus inactivating their enzymatic cis-trans peptidyl-prolyl isomerase function. Latter is required for proper folding of cellular proteins and of proteins of several viruses. Here, we summarize present knowledge on the role of cyclophilin A during coronavirus replication. We present data on the effect of cyclophilin A single nucleotide polymorphism mutants on the replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…For HCoV-NL63, we have recently shown that CypA expression is essential in CaCo-2 cells (Carbajo-Lozoya et al, 2014). Utilizing a Huh-7.5 CypA KD (knockdown) cell line, originally constructed for the study of the requirement of stable CypA for HCV replication (von Hahn et al, 2012) we found significantly reduced replication of a HCoV-229E-Renilla luciferase expressing virus (von Brunn et al, 2015). This indicates the involvement of CypA also in replication of HCoV-229E.…”
Section: Discussionmentioning
confidence: 84%
“…For HCoV-NL63, we have recently shown that CypA expression is essential in CaCo-2 cells (Carbajo-Lozoya et al, 2014). Utilizing a Huh-7.5 CypA KD (knockdown) cell line, originally constructed for the study of the requirement of stable CypA for HCV replication (von Hahn et al, 2012) we found significantly reduced replication of a HCoV-229E-Renilla luciferase expressing virus (von Brunn et al, 2015). This indicates the involvement of CypA also in replication of HCoV-229E.…”
Section: Discussionmentioning
confidence: 84%
“…Subsequently, the importance of CypA as a host factor in CoV replication was further substantiated using knockdown or knockout of CypA expression, which was achieved using a variety of approaches. In Caco-2 and Huh7.5 cells, shRNA-mediated knockdown of CypA mRNA expression to below 3% of the normal levels was reported to nearly completely block HCoV-NL63 replication (Carbajo-Lozoya et al, 2014) and reduce HCoV-229E-driven luciferase expression by 10-to 20-fold (von Brunn et al, 2015). CypA-or CypB-knockout in feline fcwf-4 cells resulted in a near-complete block of FCoV replication.…”
Section: The Potential Role Of Cyps In Coronavirus Infectionmentioning
confidence: 95%
“…Previously, CypA and/or CypB were reported to play a role in the replication of a number of arteri-and coronaviruses (Carbajo-Lozoya et al, 2014;de Wilde et al, 2013a;Tanaka et al, 2017;von Brunn et al, 2015). The degree of sensitivity to Cyp depletion appeared to differ between these viruses, but was not compared directly.…”
Section: Nidovirus Replication In Cyclophilin-knockout Cell Poolsmentioning
confidence: 99%
“…Cyclophilins were initially implicated as host factors in nidovirus replication during studies with general Cyp inhibitors such as cyclosporine A (CsA). In cell culture, the replication of a variety of coronaviruses and arteriviruses was found to be strongly inhibited by lowmicromolar concentrations of CsA and the non-immunosuppressive CsA analogs Alisporivir (ALV) and NIM-811 (Carbajo-Lozoya et al, 2014de Wilde et al, 2017ade Wilde et al, , 2013bde Wilde et al, , 2011Kim and Lee, 2014;Tanaka et al, 2012;von Brunn, 2015;von Brunn et al, 2015). Subsequently, it was established that nidovirus replication can depend specifically on CypA and/or CypB.…”
Section: Introductionmentioning
confidence: 99%